PERJANJIAN ENDORSEMENT SECARA LISAN ANTARA INFLUENCER DENGAN ONLINE SHOP (FAMOSTA SHOP) DI TINJAU DARI HUKUM PERDATA - Vira Santika; Hayatul Ismi; Meriza Elpha Darnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Article 1313 of the Civil Code concerning agreements, which states that"An agreement is an act by which one or more people bind themselves to one ormore people. Endorsement agreements between Influencers and Online Shopsverbally which often lead to defaults. The purpose of writing this thesis is first, tofind out why influencers do not carry out endorsement agreements that are madeorally in terms of civil law. Second, to find out the obstacles in verbalendorsement agreements between Influencers and online shops (Famosta Shop) interms of civil law.This type of research is sociological legal research, namely researchconducted on the identification of laws and the effectiveness of laws that apply insociety. In this case, look at the reasons for influencers not carrying out theendorsement agreement verbally and what obstacles arise from the verbalagreement. The nature of the research is descriptive which provides precise dataabout humans, conditions and other symptoms.The results of this study indicate that the reasons for influencers notcarrying out endorsement agreements verbally are carried out verbally without athird person as a witness, the influencer's limitations in carrying out agreementsand the obstacles the parties have in making verbal endorsement agreements thatoften occur come from both parties. such as the lack of online shop policies inmaking agreements, influencers do not establish good communication in carryingout agreements so that defaults occur.Keywords:Agreement-Endorsement-Influencer-Online Shop